Commentary. Saul B. Cohen: Scientific Neutrality and Selective Containment beyond the Bipolar Order - Limón López, Pedro (Geopolítica(s). Revista de estudios sobre espacio y poder, 2022)
Saul Bernard Cohen was one of the most renowned geographers in the history of the 20th century and one of the essential figures in American geopolitical thought from the second third of the Cold War to the present. His model of analysis on world division into geostrategic and geopolitical regions, as well as the emphasis on the concept of “shatterbelts” as places to deploy and emphasize containment by the United States, acquired both academic status and political influence becoming one of the most predominant approaches of the post-Cold War geopolitical order. From some premises articulated on American neorealism in the context of nuclear deterrence and the inclusion of the notion of “gateway regions”, Cohen redefined the selective containment that could — and should — be applied in a Post-Cold War world without the need of a bipolar order.